Knowledge and practice in mental health nursing care - Teresa Cristina da Silva Kurimoto; Claudia Maria de Mattos Penna; Débora Isane Ratner Kirschbaum Nitkin
ABSTRACT Objective: To understand mental health nursing care based on the concept of the subject of the unconscious proposed by Lacan. Method: A narrative study was carried out with 19 nurses, chosen based on their theoretical approach or referral by other participants, through the snowball sampling technique. The interviews were carried out in person or digitally, and were recorded and fully transcribed. Results: The analysis was carried out based on Freudian and Lacanian psychoanalysis, approaching nursing care as it acts on the body, secretions, and excretions, to distinguish it from the spirit of fineness. Effects on care are discussed, considering the subject of the unconscious with its knowledge, creating unique exits (sinthome). In this situation, professionals are required to abstain from a position of knowing what is better for the Other. Final considerations: This nursing care perspective offers contributions when discussing the centrality of the subject and words in the care process.